Agricultural Development in Indonesia: Current Problems, Issues, and Policies - Joyo Winoto; Hermanto Siregar (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2008)
After around a decade since the Asian Financial Crisis, the Indonesian economy has still experienced a relatively slow growth. The growth has tended to increase, but is considerably lower than that of the pre-crisis era. With a relatively low level and the quality of growth, the high rates of unemployment and poverty have been difficult to reduce. Despite its potential role of reducing the rates of poverty and unemployment, agricultural growth and rural development have yet tended to be stagnant. Development efforts, on both agriculture and non-agriculture, have still been concentrated in Java whereby land availability is very limited. The problems of poverty and unemployment seem to have intensified less-sustainable agricultural practices, giving rises—at least partially—to more land degradation and threats to water sustainability. To overcome the problems, the country needs sound/comprehensive agricultural and rural development policy. Effectiveness of such policy in overcoming the problems would depend much on the integration of serious efforts to enhance agricultural productivity as well as to improve rural infrastructure and social-economic institutions.